Analyze The Marketer Activity in Digital Era with Implemented Digital Ethic - Rezi Muhamad Taufik Permana; Syifa Fauziah Hamidah (Jurnal Manajemen Bisnis Performa, 2022)
Digital technology has become part of marketing activities for a marketer, every marketer is currently required to be able to implement digital marketing activities. On the other hand, the use of digital technology raises issues that are hotly discussed, especially ethical issues.This research was conducted with a qualitative descriptive approach by looking at the theories of marketing and digital ethics. This study uses secondary data contained in books, white papers, journals, articles which is the basis for a literature review. The results show that digital skills and expertise alone are not enough for a marketer. To become a reliable marketer in the digital world, it is very necessary to know and apply digital ethics.